Looking for lipases and lipolytic organisms in low-temperature anaerobic reactors treating domestic wastewater. (1st April 2022) - Bashiri, Reihaneh; Allen, Ben; Shamurad, Burhan; Pabst, Martin; Curtis, Thomas P.; Ofiţeru, Irina D.
Highlights: Metagenomics and metaproteomics were used to look for lipases and lipolytic bacteria. Bacteria might not always use lipases to degrade exogenous lipids. Lipases can be used for polyhydroxyalkanoates accumulation or degradation. fadL genes (long-chain fatty acid transporters) may not be a good biomarker for lipolytic bacteria. Abstract: Poor lipid degradation limits low-temperature anaerobic treatment of domestic wastewater even when psychrophiles are used. We combined metagenomics and metaproteomics to find lipolytic bacteria and their potential, and actual, cold-adapted extracellular lipases in anaerobic membrane bioreactors treating domestic wastewater at 4 and 15 °C. Of the 40 recovered putative lipolytic metagenome-assembled genomes (MAGs), only three ( Chlorobium, Desulfobacter, and Mycolicibacterium ) were common and abundant (relative abundance ≥ 1%) in all reactors. Notably, some MAGs that represented aerobic autotrophs contained lipases. Therefore, we hypothesised that the lipases we found are not always associated with exogenous lipid degradation and can have other roles such as polyhydroxyalkanoates (PHA) accumulation/degradation and interference with the outer membranes of other bacteria. Metaproteomics did not provide sufficient proteome coverage for relatively lower abundant proteins such as lipases though the expression of fadL genes, long-chain fatty acid transporters, was confirmed for four genera ( Dechloromonas, Azoarcus, Aeromonas and Sulfurimonas ), none of which were recovered as putative lipolytic MAGs. Metaproteomics also confirmed the presence of 15 relatively abundant (≥ 1%) genera in all reactors, of which at least 6 can potentially accumulate lipid/polyhydroxyalkanoates. For most putative lipolytic MAGs, there was no statistically significant correlation between the read abundance and reactor conditions such as temperature, phase (biofilm and bulk liquid), and feed type (treated by ultraviolet light or not). Results obtained by metagenomics and metaproteomics did not confirm each other and extracellular lipases and lipolytic bacteria were not easily identifiable in the anaerobic membrane reactors used in this study. Further work is required to identify the true lipid degraders in these systems. Graphical abstract: Image, graphical abstract